Parallel Hatching: A New Method of Hand Deformity Surgery in Epidermolysis Bullosa - Siamak Farokh Forghani, MD; Rana Irilouzadian, MD; Ali Shabbak, MD; Amir Saraee, MD (Journal of Hand Surgery Global Online)
Purpose: In dystrophic epidermolysis bullosa (EB), progressive blistering, scarring, and fusing of digits lead to mitten-hand and pseudosyndactyly in early childhood, inflicting psychosocial stress and low self-esteem in EB patients. Treatment is a challenge in the hand surgery field because of the recurring nature of this inherited disease. We aim to evaluate the results of our surgery method for the hand deformities in EB patients. Methods: We retrospectively reviewed the chart of the EB patients from 2013 to 2023 and included the patients that had the surgery by the same surgeon with the technique of parallel transverse hatching incisions in their hands with using amnion as a dressing and no grafts. The results of the surgery were assessed by using the pseudosyndactyly grading. To compare the data, t test and χ2 test were used for variables as appropriate. Results: We presented the results of our surgery method for hand deformities in EB patients. Twenty hands (11 right and 9 left hands) from 11 patients were included. The mean ± SD of grades before and after surgery in all of the patients were 2.2 ± 0.9 and 1.2 ± 1.2, respectively. The differences in grades from baseline in both left and right hands were significant (P-values of .009 and .001, respectively). Conclusions: In this method, we use parallel transverse incisions in epidermis and dermis of the palmar interphalanges without grafting. This will limit the trauma imposed on EB patients who are susceptible to reblistering and poor wound healing. Our patients demonstrated improvement in the function and appearance of their hands with up to 3 years of follow-up. Type of study/level of evidence: Therapeutic, III.